HUBUNGAN ANTARA SELF REGULATION DAN REVENGE BEDTIME PROCRASTINATION PADA MAHASISWA DI JAKARTA - Indriani Indriani; Denrich Suryadi (Fakultas Psikologi Universitas Tarumanagara, 2026)
The hectic daily routines of individuals especially in young adults, lead to a sense of dissatisfaction regarding leisure time, this causes them to choose to use their evenings as a form of “revenge” by engaging in activities they enjoy. This desire for personal time conflicts with the body’s need for rest, which can disrupt sleep patterns and is known as revenge bedtime procrastination. Revenge bedtime procrastination is a form of self-regulation failure, individuals with low self-regulation are unable to manage and adapt to long-term goals and become preoccupied with the short-term pleasures they obtain. This study aims to examine the relationship between self-regulation and revenge bedtime procrastination among college students in Jakarta. The research method employed a quantitative approach with a total of 420 participants as respondents. Data collection techniques utilized the Short Self-Regulation Questionnaire (SSRQ) and the Revenge Bedtime Procrastination Scale. The results of the analysis indicate a significant negative relationship between self-regulation and revenge bedtime procrastination (r = -0.196, p < 0.001). This suggests that the higher the level of self-regulation, the lower the level of revenge bedtime procrastination among university students. These findings suggest that improving self-regulation can reduce the incidence of revenge bedtime procrastination among college students in Jakarta. This study is expected to provide insights and knowledge particularly for college students regarding the importance of improving self-regulation and reducing revenge bedtime procrastination, which can have adverse effects on health.